ANALYZE THE ROLE OF ENTREPRENEURSHIP EDUCATION IN ENCOURAGING ENTREPRENEURIAL INNOVATION - Ulfah Muhayani; Bella Izzatun Nafsi; Indang Wandhan Sari; Hikmah Wifaqi; Wildan Fikaromil Layali (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Entrepreneurial innovation has emerged as a key driver of economic growth in numerous countries, particularly in the current era of globalization and digitalization. Education in entrepreneurship plays a vital role in equipping individuals with the necessary skills to innovate across various economic sectors, enabling them to effectively compete on a global scale. This study adopts a Systematic Literature Review (SLR) methodology, leading to the selection of 40 relevant articles for analysis. The research focuses on two primary questions: how does entrepreneurship education contribute to the development of innovative skills among entrepreneurs, and what are the essential components of entrepreneurship education that can enhance entrepreneurial innovation capabilities? The findings reveal that entrepreneurship education encompasses not only theoretical knowledge but also practical elements that are crucial in the innovation process. Additionally, social support from both family and educational institutions significantly impacts students' intentions to pursue entrepreneurship and innovation. ABSTRAK Inovasi kewirausahaan telah muncul sebagai pendorong utama pertumbuhan ekonomi di banyak negara, terutama di era globalisasi dan digitalisasi saat ini. Pendidikan dalam kewirausahaan memainkan peran penting dalam membekali individu dengan keterampilan yang diperlukan untuk berinovasi di berbagai sektor ekonomi, memungkinkan mereka untuk bersaing secara efektif dalam skala global. Penelitian ini mengadopsi metodologi Systematic Literature Review (SLR), yang mengarah pada pemilihan 40 artikel yang relevan untuk dianalisis. Penelitian ini berfokus pada dua pertanyaan utama: bagaimana pendidikan kewirausahaan berkontribusi pada pengembangan keterampilan inovatif di kalangan pengusaha, dan apa komponen penting dari pendidikan kewirausahaan yang dapat meningkatkan kemampuan inovasi kewirausahaan? Temuan tersebut mengungkapkan bahwa pendidikan kewirausahaan tidak hanya mencakup pengetahuan teoritis tetapi juga unsur-unsur praktis yang sangat penting dalam proses inovasi. Selain itu, dukungan sosial dari keluarga dan lembaga pendidikan secara signifikan berdampak pada niat siswa untuk mengejar kewirausahaan dan inovasi.